2012
DOI: 10.1371/journal.pgen.1002435
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila melanogaster Seminal Fluid Protease “Seminase” Regulates Proteolytic and Post-Mating Reproductive Processes

Abstract: Proteases and protease inhibitors have been identified in the ejaculates of animal taxa ranging from invertebrates to mammals and form a major protein class among Drosophila melanogaster seminal fluid proteins (SFPs). Other than a single protease cascade in mammals that regulates seminal clot liquefaction, no proteolytic cascades (i.e. pathways with at least two proteases acting in sequence) have been identified in seminal fluids. In Drosophila, SFPs are transferred to females during mating and, together with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
186
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 130 publications
(194 citation statements)
references
References 65 publications
8
186
0
Order By: Relevance
“…Given how little is known about the regulation of seminal fluid proteases, a model system for studying these proteins is particularly useful. We recently demonstrated that a Drosophila melanogaster seminal fluid proteolysis pathway that begins in the male during copulation, and is completed in the female following copulation, is regulated by at least two proteases (LaFlamme et al 2012). This pathway lends itself well to genetic manipulation and is therefore a useful model in which to study the regulation seminal fluid proteases.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Given how little is known about the regulation of seminal fluid proteases, a model system for studying these proteins is particularly useful. We recently demonstrated that a Drosophila melanogaster seminal fluid proteolysis pathway that begins in the male during copulation, and is completed in the female following copulation, is regulated by at least two proteases (LaFlamme et al 2012). This pathway lends itself well to genetic manipulation and is therefore a useful model in which to study the regulation seminal fluid proteases.…”
mentioning
confidence: 99%
“…In D. melanogaster, as previously described, a proteolytic pathway is initiated in the male genital tract during ejaculation whereby the trypsin-like serine protease seminase is activated, allowing for the rapid cleavage and activation of the astacin metalloprotease CG11864 (LaFlamme et al 2012), which we rename here Seminal metalloprotease-1 (gene symbol: semp1). Semp1, in turn, is required for the proteolytic cleavage of at least two downstream Sfps: ovulin (Acp26Aa) and Acp36DE (LaFlamme et al 2012).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, on the male side of the SP/SPR paradigm, Mariana Wolfner (Cornell University) described how secreted products of the male's accessory gland are required for extended SP function within mated females. She reported results of collaborative studies with François Karch's lab (University of Geneva) that show that products from each cell type in this gland are needed for long term SP persistence in mated females, and that a seminal protease is important for this persistence of SP (LaFlamme et al, 2012).…”
mentioning
confidence: 99%